Improving Dairy Cow Metabolism through Safflower Oil Supplementation - Lokenga Badinga; Richard D. Miles; Cristina Caldari-Torres (EDIS)
Data collected in Florida studies indicate that feeding fat supplements that decrease milk fat test during the early postpartum period may help minimize negative energy balance, reduce body fat mobilization, and improve blood levels of beneficial metabolic and reproductive hormones. This 3-page fact sheet was written by Lokenga Badinga, Richard D. Miles, and Cristina Caldari-Torres, and published by the UF Department of Animal Science, September 2011.